Pengaruh Durasi Waktu Aerasi Pengolahan Air Limbah dengan Sistem Lumpur Aktif (Bioflokulasi) terhadap Penurunan BOD (Biological Oxygen Demand) Air Limbah Rumah Sakit PKU Muhammadiyah Surakarta - Indriyani, Lusi; Sugiharto, Agung (Universitas Muhammadiyah Surakarta, 2022)
The hospital is one of the health service facilities as an effort to improve and maintain public health. As the population continues to increase, the need for health care facilities also increases. For hospital wastewater, in general, it is a mixture of all domestic wastewater (waste from bathrooms, kitchens, used washing water), clinical wastewater, laboratory wastewater and the results of various other activities in the hospital. The presence of domestic wastewater results in a high content of organic substances in hospital wastewater.This study uses a quantitative case study with experimental research methods in the field to determine the effect of aeration time on the reduction of BOD. From the results of the research that has been done, it can be seen from the graph above that wastewater without aeration with a residence time of t=0 hours the BOD parameter is 42.11 mg/l, in wastewater aeration with the addition of biofloc for t=1 hour the BOD value is equal to 35.28 mg/l, in wastewater aeration with the addition of biofloc for t=3 hours the BOD value is 34.98 mg/l, in wastewater aeration with the addition of biofloc for t=6 hours the BOD value is 34.88 mg/l. The activated sludge system is quite effective in wastewater treatment. The longer the residence time of wastewater aeration, the smaller the value of BOD levels. The optimal time duration for the aeration process is 8 hours, which is appropriate because the maximum time for aeration processing is 8 hours.